Two cultures of rights: the quest for inclusion and participation in modern America and Germany - Berg, Manfred; Geyer, Martin H. (Cambridge University Press, 2002)
This collection addresses key issues in the historical struggle for civil rights, political rights and social rights in the United States and Germany from the late nineteenth century to the present. Using a cross-national comparative approach, this book presents national case studies that explore the similarities and differences of conceptualizing rights on both sides of the Atlantic. This book analyses the struggle for these rights by individuals and groups and how this struggle became an essential feature not only in political discourse but also in social and political practice and culture in both Germany and the United States. More specifically, the book examines the different ways rights have been denied due to race, ethnicity, gender and sexual orientation. Considerable attention is given to the impact of Nazism and the struggle for social rights during and after World War II
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Aufsatzsammlung; Konferenzschrift -- 1997 -- Washington, DC; Geschichte 1800-2000; Bürgerrecht; USA; Deutschland